Up-regulation of CD163 expression in subpopulations of blood monocytes after kidney allograft transplantation - Čurnová, L; Mezerová, K; Švachová, V; Fialová, M; Novotný, M; Čečrdlová, E; Viklický, O; Stříž, I (Physiological research, 2020)
M2 macrophages expressing CD163 are known to suppress immune responses but have been also found in biopsies of patients with chronic kidney allograft injury associated with interstitial fibrosis. The aim of our study was to evaluate the expression of CD163 in blood monocytes, precursors of tissue macrophages, in kidney allograft recipients with uncomplicated outcome (n=94) compared with those developing acute rejection (n=44). Blood samples were collected before the transplantation and at 1 week, 1 month and 1 year. The expression of CD163 increased during the first week after the transplantation not only in classical (CD14+CD16-) but also in intermediate (CD14+CD16+) and nonclassical (CD14lowCD16+) monocytes in all patients regardless of their rejection status. In patients developing acute rejection, higher pre-transplant expression of CD163 on blood monocytes was found. In vitro experiments confirmed strong induction of membrane CD163 on monocytes together with CD206 (an alternative marker of M2 macrophages) in response to IL-10. We assume from our data that dramatic upregulation of CD163 by peripheral blood monocytes may have a pathophysiological role in early phases after kidney allograft transplantation and high pre-transplant expression of CD163 on blood monocytes might be involved in events leading to acute rejection.
Keywords: Young Adult; antigeny diferenciační myelomonocytární; Male; biologické markery; Up-Regulation; mladý dospělý; Biomarkers; Adolescent; interleukin-10; Antigens, CD; monocyty; CD antigeny; Adult; alografty; upregulace; Aged; dospělí; mužské pohlaví; senioři; Graft Rejection; receptory buněčného povrchu; Interleukin-10; CD163 Antigen; mladiství; senioři nad 80 let; lidé; ženské pohlaví; Kidney Transplantation; transplantace ledvin; Humans; makrofágy; antigen CD163; Monocytes; rejekce štěpu; Aged, 80 and over; Receptors, Cell Surface; Allografts; Female; Macrophages; lidé středního věku; Middle Aged; Antigens, Differentiation, Myelomonocytic